MENDESAIN ULANG KEWENANGAN BAWASLU DALAM MENANGANI PELANGGARAN PEMILU - ansori (Progressive Law Review, 2024)
Bawaslu's authority in preventing election violations is often constrained by the election process itself. When the election process is completed, all problems that occur during the process must also be considered complete, while Bawaslu's authority cannot be limited as long as the law does not regulate it. This is a problem in the process of resolving election violations by Bawaslu. The purpose of this study is to redescribe Bawaslu's authority in resolving election disputes, while the method used in this research is normative legal research method with the approach of legislation and concepts, the result is that Bawaslu is limited by the determination of election results and the Constitutional Court's decision, the solution is the Strengthening of Bawaslu's Authority in Handling Election Violation Disputes, and the Synchronization of the Dispute Resolution Process, This means that the Election Law requires the settlement of disputes in Bawaslu to be completed first before the process in the Constitutional Court (MK) in order to prevent overlapping decisions between Bawaslu and the Constitutional Court, and the most important thing is to provide sufficient time and authority for Bawaslu to carry out its duties, so that no one interprets any restrictions on Bawaslu's authority in resolving disputes over election violations.